#TITLE_ALTERNATIVE# - SEPTINA (NIM 13303022); Pembimbing : Dr. Ir. Nugraha dan Dr. Brian Yuliarto, WILMAN
Titanium dioxide (TiO2) is one of the most studied metal oxide especially in its application for energy and environment areas. TiO2 is well known as a main semiconductor oxide in dye-sensitized solar cell (DSSC) as well as a photocatalyst material for pollutant decomposition. For those applications, TiO2 is necesarry to exhibit high surface area. Mesoporous material (2-50 nm in pore size), with its high surface area, homogenous pore distributions, dan ordered pores characteristics, is ideal structure for those TiO2 applications. In this research, nanocrystal mesoporous TiO2 powder was synthesized using sol-gel method, with TiCl4 as a precursor in methanol/ethanol solution. Block copolymer PluronicPE 6200 and Pluronic PE 8100 were used as a pores template to form mesoporous structure. From XRD result, it is shown that 400 degrees C and 450 degrees C calcination temperature resulted in nanocrystal TiO2 with anatase phase for methanol solvent, and bicrystal anatase-rutile phase for ethanol solvent on low relative humidity condition. Based on N2 adsorption characterization (BET method), generally TiO2 samples have high surface area compared to commercialized nano-TiO2 about 80-108 m2/g. From Small-angle Neutron Scattering (SANS) patterns, it is shown that TiO2 samples using block copolymer Pluronic PE 6200 have mesoporous structure which is the pore ordering degree depend on calcination temperature.